2010
DOI: 10.1038/ijo.2010.124
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen inhibits NPY secretion through membrane-associated estrogen receptor (ER)-α in clonal, immortalized hypothalamic neurons

Abstract: Objective: Estrogen (E 2 ) has an inhibitory effect on food intake by acting centrally in the hypothalamus, although it is not clear which hypothalamic neurons are involved in this process. Earlier studies from our lab and others have implicated neuropeptide Y (NPY) as an important central anorexigenic target of E 2 . This study was designed to investigate whether E 2 can directly regulate NPY secretion and examine the cellular mechanisms and receptors responsible for this anorexigenic action of E 2 . Design: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 34 publications
(43 reference statements)
1
40
0
Order By: Relevance
“…The ARH also mediates energy balance through NPY and ␤-endorphin. Estradiol is anorexic and has been reported to reduce NPY mRNA in vivo and inhibit NPY release from immortalized hypothalamic neurons (Silva et al, 2010;Dhillon and Belsham, 2011). In terms of feeding regulation, NPY and ␤-endorphin neurons appear to have a parallel organization with both sets of neurons affecting melanin-concentrating hormone neurons in the lateral hypothalamus (Schwartz and Gelling, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The ARH also mediates energy balance through NPY and ␤-endorphin. Estradiol is anorexic and has been reported to reduce NPY mRNA in vivo and inhibit NPY release from immortalized hypothalamic neurons (Silva et al, 2010;Dhillon and Belsham, 2011). In terms of feeding regulation, NPY and ␤-endorphin neurons appear to have a parallel organization with both sets of neurons affecting melanin-concentrating hormone neurons in the lateral hypothalamus (Schwartz and Gelling, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, E 2 reduces secretion of the peptide from immortalized hypothalamic neurons (11). We have shown that E 2 decreases the membrane excitability of NPY/AgRP neurons, at least partially, through increasing the expression of KCNQ5 channels, which augments the M-current (36).…”
mentioning
confidence: 87%
“…4C). ER␣ has been shown to complex with PI3K in hypothalamic and cortical neurons (11,43), so we decided to test specifically if the attenuation of the GABA B response could be mimicked by the ER␣-selective agonist PPT (15). Indeed, PPT (100 nM) replicated the effects of E 2 to attenuate the GABA B response in NPY/AgRP neurons by 46.7 Ϯ 13.8% (n ϭ 4, P Ͻ 0.001; Fig.…”
Section: E634 Rapid Estrogen Signaling In Npy/agrp Neuronsmentioning
confidence: 99%
“…The anorexigenic hormone leptin has a stimulatory effect on POMC, and an inhibitory effect on NPY and AgRP (Belsham et al 2004;Cowley et al 2001). Estradiol has a similar anorexigenic effect (Wade 1972;reviewed in Gao and Horvath 2008), increasing POMC mRNA in the ARC of mice, and inhibiting NPY secretion in immortalized hypothalamic neurons (Dhillon and Belsham 2011;Gao et al 2007). Estrogen receptor alpha (ERa) colocalizes with POMC in the ARC, and may be regulating the expression of POMC in the hypothalamus (de Souza et al 2011).…”
Section: Interactions Between Sex Hormones and Food Intakementioning
confidence: 99%
“…ACC acetyl-CoA carboxylase, AgRP agoutirelated peptide, AICAR 5-Aminoimidazole-4-carboxyamide ribonucleoside, AMPK AMP-activated protein kinase, AR androgen receptor, DHT dihydrotestosterone, ERa estrogen receptor alpha, FFAs free fatty acids, GHSR growth hormone secretagogue (ghrelin) receptor, InsR insulin receptor, LepR leptin receptor, mTOR mammalian target of rapamycin, NPY neuropeptide Y, POMC pro-opiomelanocortin, STAT3 signal transducer and activator of transcription 3. Based on data from: Cota et al 2006;Dhillon and Belsham 2011;Diéguez et al 2011;Minokoshi et al 2004;Nohara et al 2011 downregulating NPY and AgRP activity and upregulating POMC (Schwartz et al 2000;Zhang et al 1994). Leptin generally has an antagonistic relationship with (and opposite physiological effects of) the orexigenic hormone ghrelin.…”
Section: Leptin and Its Role In Food Intakementioning
confidence: 99%